Penyuluhan Tentang Gerakan Masyarakat Hidup Sehat - Kusumaningsih, Rila; Rima Rinekasari (Insan Kreasi Media, 2024)
The Healthy Living Community Movement (GERMAS) is an initiative The Healthy Living Community Movement (GERMAS) is an initiative introduced to encourage people to be more careful in maintaining their health. This movement covers various aspects, from managing physical and mental health, to managing a healthy environment. This health education aims to provide an understanding of how to live a healthy life in a healthy environment. This movement also aims to reduce environmental pollution that can cause disease, such as air pollution and polluted water. This can be done in various ways, starting from increasing public understanding of a healthy environment and increasing access to environmental services. In this extension we use the socialization method via PowerPoint media. Efforts to create a healthy society require active participation from all parties, especially the entire community. The Healthy Living Community Movement can play an important role in reducing health-related diseases such as heart disease, diabetes and cancer. And helps reduce environmental pollution that can cause disease. In this journal, we will discuss the implementation of the Healthy Living Community Movement and the appropriate steps that can be used to encourage people to be more competent in maintaining health.